Biomechanical effects of loading methods on the patellofemoral joint during stair climbing: based on statistical parametric mapping analysis - Zhang, Hongwen; Zhang, Xingchen; Ma, Jing; Sun, Na; Zhang, Litai; Gao, Yuan (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionStair negotiation with external loads imposes substantial demands on the structural and functional integrity of the patellofemoral joint. Current research predominantly focuses on singular loading modalities or level walking conditions, often employing discrete time-point comparisons. This study innovatively employs Statistical Parametric Mapping (SPM) to systematically analyze patellofemoral biomechanical characteristics during stair negotiation with different load-carrying strategies.MethodsTwenty healthy males performed stair negotiation tasks under shoulder-load carriage (SLC) and hand-carry carriage (HCC) conditions (15 kg). Kinematic (200 Hz), kinetic (2000 Hz), and electromyographic (2000 Hz) data were synchronized to compute patellofemoral joint stress(PFJS), center of pressure (COP) trajectories, and muscle co-activation indices across stair phases.ResultsHCC generated significantly greater patellofemoral joint stress during most stair phases compared to SLC (P < 0.05), while SLC exhibited transient stress elevation only during initial double-support phase.DiscussionHCC particularly increased joint stress during single-support and second double-support phases, with concomitant increases in COP displacement distances and reduced lower-limb co-cativation indices (CCI) collectively compromising joint stability. Despite transient stress spikes during initial double-support, SLC maintained kinetic chain equilibrium through shorter external moment arms. These findings recommend prioritizing proximal symmetric loading modes complemented by targeted vastus medialis training to enhance patellar stability, thereby reducing both patellofemoral joint stress concentrations and low back pain risks.